Factor structure and psychometric properties of the 100-item and 42-item Qingnian Zhongguo Personality Scale (QZPS). - Wu, Junwei. (2010)
Two studies were conducted to explore the factor structure and psychometric properties of two scales derived from the Big Seven Model of Chinese personality. The Big Seven personality model was developed by Wang and Cui (2005a, 2005b) based on the conceptualization and manifestation of the Chinese personality structure. Wang and Cui (2005b) developed a 180-item Qingnian Zhongguo Personality Scale (QZPS) to assess the Chinese personality.